Pengaruh Karakteristik Konsumen terhadap Informasi Obat yang Diharapkan: Studi potong lintang di Apotek Wulan Pekutatan - Jati, Gusti Bagus Krisna Arum; Agustini, Ni Putu Dewi; Antari, Ni Putu Udayana (Jurnal Ilmiah Medicamento, 2023)
Health workers and patients have different perceptions regarding the information that needs to be provided when dispensing medication. Differences in perception can make ineffective communication, so providing drug information in pharmaceutical services is not optimal. This research aims to determine the influence of consumer characteristics on the drug information expected at the Wulan Pekutatan Pharmacy. The research used a cross-sectional approach at the Wulan Pekutatan Pharmacy, Jembrana Regency, Bali Province. Samples were taken using the convenience sampling technique. Respondents are patients willing to complete a questionnaire, are over 17 years old, can read and write, and have previously visited a pharmacy. The chi-square test determines consumer characteristics that influence the expected drug information according to patient characteristics. The research succeeded in collecting 96 respondents. There are twelve types of information asked of respondents. The results showed that the type of information respondents expected significantly differed (P<0.05) in several characteristics. Patient groups who choose different types of information include male and female patients, adult and elderly patients, health workers and non-health workers, married patients, and unmarried/divorced patients, patients with income levels above the regional minimum wage and below the minimum wage. It can be concluded that consumer characteristics influencing the drug information they expect include gender, age, occupation, marital status, and income.